ESTUDO DA INFLUÊNCIA DAS CONDIÇÕES DE TRATAMENTO TÉRMICO NAS PROPRIEDADES DE FILMES DE WO3 DEPOSITADOS POR DC SPUTTERING - Andrea Alves Boaventura (2023)
ABSTRACT One of the main problems afflict modern society is the uncontrolled emission of toxic gases into the environment. In this way, the development of resistive sensor technology, aiming to make them more efficient and cheaper, has been the focus of several research groups and industry in recent years. The development of this technology is essential for, among other applications, monitoring air quality. Among the most promising materials to be applied in this type of sensor, tungsten trioxide (WO3) stands out for having several interesting properties such as excellent selectivity, fast response, easy construction, flexibility and stable physical-chemical properties. Although it is possible to find several works involving WO3 applied to resistive gas sensors, further studies are still needed to enable its practical application. The main obstacles related to the application of WO3 in resistive gas sensors are related to selectivity and chemical stability. In this context, the main objective of this work was to evaluate how different thermal treatment parameters influence the properties of WO3 films deposited by the DC Magnetron Sputtering technique. The films were grown at room temperature on a glass substrate, in an atmosphere of oxygen and argon. After deposition, the films were thermally treated at 300°C, 400°C, 500°C and 600°C, both at atmospheric pressure and at low pressure (10 mtorr). Results of the structural, vibrational, optical and electrical characterizations of the films, obtained through Raman spectroscopy, x-ray diffraction and visible ultraviolet spectroscopy measurements will be presented. Keywords: Tungsten Oxide, DC Magnetron Sputtering, Thermal Treatment, Gas Sensors.